Composição de obras para pandeiro brasileiro solo no contexto da música de concerto - Biagioni, Vitor Lyra (2022)
The Brazilian pandeiro is configured as a national symbol and is internationally recognized as a genuinely Brazilian instrument. Its function is normally to perform rhythmic conduction. The present research aims at the adaptation and use of the instrument in compositional languages of concert music, a musical environment in which the tambourine has been little explored. Together, we inserted the instrument in the role of soloist, aiming at the transformation of the traditional functionality used (accompanist). As a result, we present seven solo works that use and employ these musical concepts.